Rates and causes of deforestation in Indonesia: towards a resolution of the ambiguities - Sunderlin, William D.; Resosudarmo, I.A.P. (Center for International Forestry Research, 1996)
There have been several major research efforts on the rate and causes of Indonesia's deforestation in recent years and much associated literature, but there is still no consensus in the research community on these issues. This paper reviews the areas of uncertainty and confusion, and proposes questions that must be answered to get a better grasp of the subject. Among the key questions are: (1) How are we to define "forest", "deforestation" and "agency” in the context of Indonesia? (2) What are the socio-economic characteristics and land-use practices of the various agents that have been lumped under the term "shifting cultivation" ? (3) Is the relationship between increasing population density and loss of forest cover causal or incidental? (4) Why do some concessionaires appear to manage their sites relatively well, while many others do not? (5) What have been the net forest cover effects of macro-economic restructuring and changes of commodity prices since the early 1980s? Guidelines are proposedfor improved research on the rate and causes of forest cover change. The paper closes noting the need to rise above a tendency to seek mono-causal explanations.Cogent explanations will necessarily be complex, since the causes reside in long-standing and broad socio-economic forces.